Analisis Penerapan Jual Beli Syariah pada Usaha Pedagang Kaki Lima (PKL) di Terminal Leuwiliang Kabupaten Bogor - Salwa Aini Febrianti; Dedi Junaedi; Sukarna Sukarna (VISA: Journal of Vision and Ideas, 2021)
This study aims to determine whether the street vendors at the Leuwiliang terminal know and apply sharia buying and selling in their daily marketing strategies and to find out whether the implementation of sharia buying and selling in their marketing strategies has an effect on the sales of street vendors. at Leuwiliang Terminal. To answer this question, the author uses descriptive qualitative research, namely an analysis of data that is explanatory and informational data that will be associated with theories and concepts that will be discussed in qualitative research and provide conclusions from this research. Data collection techniques used are observation, interviews, and documentation, the data sources used are primary and secondary data. Furthermore, data analysis consists of data collection, data reduction, data presentation, and drawing conclusions. Most of the street vendors in Leuwiliang Terminal Bogor do not know about buying and selling sharia, but when they are explained about buying and selling sharia and being asked again whether they apply sharia buying and selling in their daily buying and selling activities? The traders answered that they applied it in their daily buying and selling activities. And the street vendors at Leuwiliang Terminal are of the opinion that the implementation of sharia buying and selling has little effect on the sales of these street vendors. Keywords: buying and selling sharia, marketing strategy, street vendors